Winter maintenance service levels on cycleways. - Bergström, Anna (My University, 2000)
This Licentiate Thesis summarises the first two years of work in the PhD project "Effects on cycling of road maintenances and operation". The main purpose of the project is to evaluate the possibility of increasing the number of cyclists through an improved winter maintenance service level on cycleways. Car-based transport has a very wide range of impacts upon society and the broader environment. A reduction of motor traffic especially in urban regions would therefore be desirable. This could be achieved by increasing cycling as a means of personal travel. From an environmental perspective, it is especially important to reduce the number of short car trips, since they are responsible for a relatively large amount of the traffic emissions, which is particularly true in winter due to frequent cold starts. By improving winter maintenance in cycleways there seems to exist great possibilities to increase cycling frequency during winter. The maintenance service level is also important for the safety of cyclists. Maintenance methods better applied to cycleways are available today but need to be used more frequently. Also methods to monitor the winter road condition on cycleways, both subjective and objectively, need to be developed. This thesis presents available methods possible to use on cycleways. A subjective method to observe road condition on cycleways is developed based on a method for roadways. Also, an objective method, measurements of friction, applicable on cycleways is tested and evaluated. Available methods for winter maintenance on cycleways are summarized und unconventional methods for snow clearance and deicing are compared to traditional methods. A travel behavior survey and literature reviews have been conducted to describe the factors important for the mode choice during winter and also to find the feasible potential in winter cycling through an improved winter maintenance service level on cycleways.
Keywords: Individualverkehr; Fahrradverkehr; Fahrradweg; Wartung; Straßenzustand; Winterdienst; Verkehrsmittelwahl; Befragung; Fahrradförderung; Radverkehrsförderung